1977
DOI: 10.1111/j.1365-2222.1977.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE, parasites and asthma in Tanzanian children

Abstract: Two rural Tanzanian primary schools were surveyed to test the hypothesis that parasitic infestation prevents the development of asthma. 242 pupils were interviewed to determine the prevalence of pupils with recurrent episodes of wheezing. The nineteen pupils so discovered had more exercise-induced bronchial lability than equivalently exercised controls. More girls (12-8%) than boys (3-3%) had asthma. In one school, 77% of the controls had faecal parasites, mainly Ascaris spp., and in the other school 55% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In Africa, a school survey in Nigeria showed a rate of 2.4 % (Sofowora and Clarke, 1969), and Carswell et al (1977) reported a rate of 7.8% in a group of Tanzanian children. These estimates, and those of the present series, suggest that bronchial asthma is as common a condition in Ibadan children as it is in European or Australian children.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, a school survey in Nigeria showed a rate of 2.4 % (Sofowora and Clarke, 1969), and Carswell et al (1977) reported a rate of 7.8% in a group of Tanzanian children. These estimates, and those of the present series, suggest that bronchial asthma is as common a condition in Ibadan children as it is in European or Australian children.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence on whether an individual's parasite burden plays a role in the pathogenesis of atopy (hygiene hypothesis), 12,13,[31][32][33] and if so, whether this is protective 14,15,[34][35][36][37][38][39] or promotes allergy. 16,[40][41][42] A role for parasites in the pathogenesis of VKC was suggested by the observed beneficial effect of anti-parasitic medication on the course of the disease, and the larger gastrointestinal parasite burden found in stools of VKC patients in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Many studies of allergic diseases show a rural environment to be protective but the mechanism of this effect is unknown. 10,11 There are conflicting reports on the effect of parasitic intestinal load in the pathogenesis of atopy, 12,13 and whether helminthiasis is protective 14,15 or a risk factor for allergy. 16 Anti-parasitic treatment was reported to improve the course of VKC in two case series, 8,17 and a hospital-based study in Nigeria showed that patients with VKC had a larger intestinal parasite load in their stools than unaffected controls.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] However, generally elevated levels of IgE occur in patients with atopic diseases and individuals infected with helminth parasites. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Studies on the worm-atopy relationship have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have suggested that parasite-induced IgE does not protect against allergic reaction because of the high turnover of IgE on mast cells, and that helminth-induced nonspecific IgE is too small to block all Fc receptor sites on mast cells. [22][23][24][25][26][27] This article assesses the prevalence of helminth-specific IgE among atopic subjects with nonhel-minthic allergen-specific IgE. In addition, serum levels of polyclonal (total) IgE were determined in atopic subjects with and without helminth-specific IgE.…”
mentioning
confidence: 99%